Differences in ERP Value between Iberian Manufacturing and Services SMEs - Ruivo, Pedro (2018)
Ruivo, P., Rodrigues, J., Johansson, B., Oliveira, T., & Rebelo, J. (2017). Differences in ERP Value between Iberian Manufacturing and Services SMEs. In Procedia Computer Science (Vol. 121, pp. 707-715). (Procedia Computer Science). DOI: 10.1016/j.procs.2017.11.092